2022
DOI: 10.17925/ee.2022.18.2.116
|View full text |Cite
|
Sign up to set email alerts
|

Use of Continuous Glucose Monitoring in Older Adults: A Review of Benefits, Challenges and Future Directions

Abstract: Many new technologies have been developed over the past decade, and these have substantially changed the way diabetes is managed. Continuous glucose monitoring is now the standard of care for many people living with diabetes, and among its numerous benefits, it has been shown to improve glycaemic outcomes and enhance quality of life. Older adults carry a high burden of diabetes and have a high risk of hypo-glycaemia and hypo-glycaemic unawareness, and continuous glucose monitoring can help to improve glycaemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 35 publications
(62 reference statements)
0
17
0
Order By: Relevance
“…Further, recommendations for implementation of CGM in older adults remain largely undefined, which might negatively affect HCPs confidence to implement diabetes technology in this population. 9 Individuals using CSII might be more prone to technology or might be treated in a diabetes centre that has more experience in utilizing diabetes technologies in older adults. Previous publications have emphasized on the importance of human factors engineering and research on actual everyday use of diabetes technologies in different groups of users (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, recommendations for implementation of CGM in older adults remain largely undefined, which might negatively affect HCPs confidence to implement diabetes technology in this population. 9 Individuals using CSII might be more prone to technology or might be treated in a diabetes centre that has more experience in utilizing diabetes technologies in older adults. Previous publications have emphasized on the importance of human factors engineering and research on actual everyday use of diabetes technologies in different groups of users (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Older adults carry a high burden of diabetes: increased risk of hypoglycaemia and hypoglycaemia unawareness can have detrimental effects in this vulnerable population 7,8 pointing towards potential benefits of CGM use. 9,10 Reducing the risk of hypoglycaemia is a major treatment goal for older adults with diabetes. 11 A small number of clinical studies specifically in older populations have pointed out that CGM may reduce hypoglycaemia in people with type 1 12,13 and type 2 diabetes, 14 and can lead to greater reductions in HbA1c compared with a non-CGM control group.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some people quit using CGM due to difficulties such as painful insertions, wearing several devices on small bodies, obtrusive alarms, data gaps, skin and adhesive issues, and trouble analyzing the volume of data produced by CGM [4] . It has been demonstrated that those with diabetes who use CGM experience improved glycemic results and quality of life [5] , but the lifespan of the biosensors is short, making them expensive. Patients and medical practitioners may struggle to interpret CGM data, and routine maintenance may be required, making it difficult for many patients to use CGMs.…”
mentioning
confidence: 99%